Pengaruh Jumlah Penduduk, Penduduk Miskin dan Penganguran Terbuka terhadap Pertumbuhan Ekonomi di Kota Banjarbaru - Erlina; Suherty, Lina (JIEP: Jurnal Ilmu Ekonomi dan Pembangunan, 2019)
This Research was conducted to (1) analyze the Influence of Population, PoorPopulation, and Open Unemployment on Economic Growth in Banjarbaru city ; (2) tofind out what factors are most dominant in influencing economic growth ini the city ofBanjarbaru.This research was conducted in the city of Banjarbaru with data from thecentral Kalimantas Statistics Agency that can be used indata processing. Data isprocessed using multiple regression analysis (Multiple Regression Analysis) with F Testand T Test.The result of this study prove a positive relationship betwaan the level ofpopulation and economic growth. This shows that the greater the level of population willincrease economic growth in the city of Banjarbaru.